Multiple Epidermal Inclusion Cysts of Epiglottis - KC, A. K.; Shrestha, B. L. (Kathmandu University Medical Journal, 2021)
Epiglottic cysts are benign laryngeal lesions. Though congenital cysts are often life-threatening, they are usually painless and symptomless in adults, or present with slight, though perceptible, interference with either swallowing or speaking or respiration. Early recognition and diagnosis by routine mirror laryngoscopy is advocated. Prompt removal or draining is the treatment. This is a case report of 42-year-old woman with complaints of feeling of something in throat, sleep apnoea and hoarseness, who on routine mirror laryngoscopy was found to have two large cysts arising from the free border of the epiglottis. The final histopathology reported the cysts as epidermal inclusion cysts.